Case Report: Semantic Variant Primary Progressive Aphasia With Impaired Verbal Word Discrimination - Kawakami, Nobuko; Morita, Ayumi; Kanno, Shigenori; Ogawa, Nanayo; Kakinuma, Kazuo; Saito, Yumiko; Kobayashi, Erena; Narita, Wataru; Suzuki, Kyoko (Frontiers in Neurology, 2022)
Some patients with primary progressive aphasia (PPA) present with various types of hearing deficits. Research on the auditory function and speech sounds in PPA, including temporal, phonemic, and prosodic processing, revealed impairment in some of these auditory processes. Many patients with PPA who present with impaired word recognition subsequently developed non-fluent variant PPA. Herein, we present a patient with semantic variant PPA (svPPA) who demonstrated impaired verbal word discrimination. Audiological examinations revealed normal auditory brainstem responses and slightly impaired pure-tone perception. By contrast, verbal word discrimination and monosyllable identification were impaired, and temporal auditory acuity deteriorated. Analyses of brain magnetic resonance images revealed a significant decrease in the gray matter volume in bilateral superior temporal areas, predominantly on the left, compared with those of patients with typical svPPA, which appeared to be associated with impaired word recognition in our patient.